A survey on the attitude of college students to the privacy right as opposed to the right to know - Ghotbi, Nader (Bangladesh Journal of Bioethics, 2020)
There are times when two essential human rights may appear to be in conflict, or need to be balanced against one another. This paper examines the right of a party, such as officials, a group of people or an individual, to ‘privacy and confidentiality’ when others may have a conflicting ‘right to know’ about them. Although similar conflicts have been studied by other researchers, there is still controversy over the rightful balance in situations driven by new information and communication technologies. I conducted a survey on the attitude of college students to the privacy right versus the right to know using an actual case at the university. First, I asked the students if they believed protecting the privacy of a married teacher who had fathered a child with a student was more important than the right of the school to know. Second, I asked if they believed a child born to a single mother in such a relationship has the right to know about his father, or the single mother has the right to keep that information confidential. Third, I asked the students if they believed in general that the ‘right to privacy and confidentiality’ was more important or the ‘right to know’. This paper reports on the results of this survey on 222 students at an international university in Japan.